The potential of Dayak tribal herbal leaves as an anti-breast cancer agent: In silico approach - Kellik Setiawan Volta; Affan Ali Murtadlo Ahmad; Nur Muhammad Ansori Arif; Dhea Kharisma Viol; Dayu Rahma Turista Dora (BIO Web of Conferences)
Breast cancer is one of the leading causes of mortality among women worldwide, prompting the exploration of alternative, natural therapies. This study examines the anti-breast cancer potential of traditional herbal plants used by the Dayak tribe, particularly Kleinhovia hospita Linn. Through in silico approaches, the study investigates the cytotoxic effects and binding affinities of key compounds, such as Scopoletin, Quercetin, and Eleutherol, with breast cancer-related proteins. Molecular docking analysis demonstrated that Quercetin and Eleutherol exhibit high binding affinities (−9 and −8 kcal/mol, respectively) with target proteins, indicating significant potential for inhibiting cancer cell proliferation by targeting proteins like EGFR, JNK, and NUDT5. The drug-likeness analysis confirmed that Quercetin and Eleutherol meet criteria for further therapeutic exploration. These findings suggest that compounds from Dayak tribal plants could be viable anti-cancer agents, providing a scientific foundation for developing culturally relevant and effective treatments for breast cancer. Further research is recommended to isolate and evaluate the bioactive compounds in preclinical and clinical settings. This work supports the potential of traditional Dayak herbal medicine as a natural therapeutic strategy against breast cancer.